Structure and radiation-shielding characteristics of BTO/MnZnFeO ceramic composites. (March 2023) - Hannachi, E.; Sayyed, M.I.; Slimani, Y.; Almessiere, M.A.; Baykal, A.; Elsafi, M.
Abstract: There is considerable demand at present for new, non-toxic, reproducible, and cheap materials that can function effectively as γ-ray shields. This work reports the synthesis of novel BTO/MnZnFeO ceramic composites via cost-effective and environmentally friendly approaches, and examines their crystal structure and performance in terms of shielding against γ-rays. The results of X-ray diffraction indicated that bi-phasic ceramic composites underwent no chemical reaction within the MnZnFeO and BTO phases. The size of the crystallite was determined by the Scherrer formula, and decreased as the MnZnFeO content of the composite increased. The ceramics prepared in the form of pellets were exposed to γ radiation. The authors also experimentally studied the coefficient of linear attenuation, the half-value, the average tenth values, and the ratio of radiation absorption of the fabricated BTO/MnZnFeO ceramic composites. The results verified improvements in the parameters of attenuation with the addition of MnZnFeO to the BTO ceramics. The linear attenuation coefficients (LACs) of 5%, 10%, and 20% MnZnFeO at 0.662 MeV were 0.480, 0.502, and 0.546 cm −1, respectively. The half-value layer (HVL) of S1 was 0.048 cm at 81 keV, and increased to 0.876 cm at 0.356 MeV, while the HVL of S2 was 0.0475 cm at 81 keV, increased to 0.844 cm at 0.356 MeV, and was approximately 2 cm at 1.333 MeV. The values of the average tenth value layer (TVL)av were 0.16 cm at 81 keV and 2.77 cm at 0.356 MeV, and increased with the radiation energy to reach 4.5 and 6.8 cm at energies of 0.662 and 1.333 MeV, respectively. The results of our experiments thus verified the impressive performance of the BTO/MnZnFeO ceramic composites in terms of shielding against γ radiation for photons with energy lower than 100 keV. Graphical abstract: Image 1 Highlights: Synthesis of novel BTO/MnZnFeO ceramic composites. X-ray diffraction indicated the formation of bi-phasic ceramic composites. γ-ray radiation shielding properties of the ceramics were experimentally assessed. The RAR increased from 76.36% to 76.79% and 77.62% as MnZnFeO content increased. Good performance of BTO/MnZnFeO composites for the photon's energy <100 keV.